Simplified Indirect Model Predictive Control Method for a Modular Multilevel Converter - Minh Hoang Nguyen; Sangshin Kwak (IEEE Access, 2018)
Demand for modular multilevel converters (MMCs) has been steadily increasing for utilization in medium- to high-power applications because of qualities such as high modularity, easy scalability, and superior harmonic performance. Furthermore, there has been a growing trend toward utilizing model predictive control for MMCs due to its simplicity, good dynamic response, and ease of multi-objective control. However, the rise in computational load leads to a great drawback when increasing the number of submodules (SMs). This paper presents an approach to reducing the computational load and using on-state SMs and circulating currents, by preselecting the number of SMs inserted in the upper and lower arms. This approach is based on using the number of on-state SMs and the circulating current, to compute the number of SMs inserted in the upper and lower arms, which is evaluated in the next sampling instant. This facilitates a significant reduction in the number of control options and the computational load. A sorting algorithm is used to retain the balancing capacitor voltages in each SM, while the cost function guarantees the regulation of the ac-side currents, arm voltages, and MMC circulating currents. Simulation and experiment results validate the performance of the proposed approach.